Norma DRIS e faixas normais de nutrientes foliares para a cultura da atemoia ‘Thompson’ - dos Santos, Eduardo Maciel Haitzmann; Rozane, Danilo Eduardo [UNESP] (FapUNIFESP (SciELO), 2017)
Atemoya, an interspecific hybrid belonging to Annonaceae family, is the outcome of a cross between cherimoya (Annona cherimola Mill.) and Custard apple (Annona squamosa L.). In light of the current shortage of scientific data on the nutritional management techniques for this fruit, the need to develop and apply a specific methodology becomes crucial. From the variety of plant diagnostic tools available, the DRIS method was selected, for use in the commercial cultivation of the ‘Thompson’ cultivar of atemoya located in the São Paulo State, municipalities of Itapetininga, Piedade, Pilar do Sul and Salto de Pirapora. Normal nutrient ranges were determined to interpret the levels of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn in the culture through statistical regression analysis and samples of leaf dry matter, with their respective DRIS indices. Although the general index of the nutritional balance of DRIS disallowed establishing a link with productivity, this study achieved it based on the standard of determining normal ranges for cognate macronutrients to the ones cited in the literature.
DRIS standard and normal ranges of foliar nutrients for the culture of ‘Thompson’ atemoya
Keywords: Annonaceae; Foliar diagnosis; Mineral nutrition; Nutritional balance